Utilization of Discrete Event Simulation in Business Processes Management Projects: a Literature Review - Bosilj Vukšić, Vesna; Pejić Bach, Mirjana; Tomičić-Pupek, Katarina (Journal of Information and Organizational Sciences, 2017)
Discrete event simulation (DES) software is often used in business process management (BPM) projects, in order to support modeling, change and automatization of process modeling. However, the current research lacks systematic overview of the benefits and pitfalls of using DES software for BPM. The goal of this paper is to provide a systematic analysis of research paper related to the operations research, computer science, business and management that report the usage of DES in BPM projects, in order to shed some light in this area. Results of this analysis could be useful to academics and business practitioners in their projects.